Friction welding of Al-Cu-SiC composite to AISI 304 austenitic stainless steel - Özdemir, Niyazi; Balaban, Zülküf (Niyazi ÖZDEMİR, 2017)
The present study investigates the feasibility of joining an aluminium matrix composite reinforced with 5, 10 and 15 vol. % of SiCp particles to AISI 304 austenitic stainless steel by using friction welding technique. In the present study, optical and electron microscopy as well as lap shear strength test and microhardness measurements were used to evaluate the quality of bonding of Al-Cu-SiC and AISI 304 austenitic stainless steel joints produced by friction welding
Keywords: Engineering; Mühendislik